Contact-Style magmatic sulphide mineralisation in the Labrador Trough, northern Québec, Canada: Implications for regional prospectivity - Smith, William Daniel; Maier, Wolfgang D.; Bliss, Ian (Canadian Journal of Earth Sciences, 2020)
The Labrador Trough in northern Québec is currently the focus of ongoing exploration for magmatic Ni-Cu-PGE sulphide ores. This geological belt hosts voluminous basaltic sills and lavas of the Montagnais Sill Complex, which are locally emplaced amongst sulphidic metasedimentary country rocks. The recently discovered Idefix PGE-Cu prospect represents a stack of gabbroic sills that host stratiform patchy net-textured sulphides (0.2 to 0.4 g/t PGE + Au) over a thickness of ~ 20 m, for up to 7 km. In addition, globular sulphides occur at the base of the sill, adjacent to the metasedimentary floor rocks. Whole-rock and PGE geochemistry indicates that the sills share a common source and that the extracted magma underwent significant fractionation before emplacement in the upper crust. To develop the PGE-enriched ores, sulphide melt saturation was attained before final emplacement, peaking at R factors of ~ 10,000. Globular sulphides entrained along the base of the sill ingested crustally-derived arsenic and were ultimately preserved in the advancing chilled margin.